ECONOMIC DEVELOPMENT OF ISLAMIC BOARDING SCHOOLS IN WEST JAVA: INDEPENDENCE AND SUSTAINABILITY - Muhibah, Iis; Faisal, Deni (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
Islamic boarding school-based economic development leverages these schools to drive an independent economy through business units. This research aims to assess economic growth in West Javas Islamic boarding schools using qualitative descriptive methods, which outline factual situations and problems. The study found several Islamic boarding schools in West Java operate business units, including cooperatives, building rentals, and Santri Marts. However, economic development is slow due to limited business expertise among staff and the reliance on profit-sharing for business management, reducing the need for extensive control. Historically, Islamic boarding schools have focused primarily on education and religion, but since the 1970s, some have started to address social issues, including economic and political challenges. With 4,328 Islamic boarding schools and over 5 million students in West Java, there is significant economic potential. To harness this, the West Java Islamic Boarding School Cooperative Center (Kopontren) and the West Java Regional Office of the Ministry of Religion (Kemenag) organize business internships for 204 students. Empowering these schools through economic development can create greater independence and effectively leverage the vast student population.